Associations of the dietary World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) recommendations with patient-reported outcomes in colorectal cancer survivors 2–10 years post-diagnosis: a cross-sectional analysis. Issue 10 (28th May 2021) - Kenkhuis, Marlou-Floor; van der Linden, Bernadette W. A.; Breedveld-Peters, Jose J. L.; Koole, Janna L.; van Roekel, Eline H.; Breukink, Stéphanie O.; Mols, Floortje; Weijenberg, Matty P.; Bours, Martijn J. L.
Abstract: The World Cancer Research Fund and American Institute for Cancer Research (WCRF/AICR) advise cancer survivors to follow their lifestyle recommendations for cancer prevention. Adhering to these recommendations may have beneficial effects on patient-reported outcomes after a cancer diagnosis, but evidence is scarce. We aimed to assess associations of the individual dietary WCRF/AICR recommendations regarding fruit and vegetables, fibre, fast foods, red and processed meat, sugar-sweetened drinks and alcohol consumption with patient-reported outcomes in colorectal cancer (CRC) survivors. Cross-sectional data of 150 stage I–III CRC survivors, 2–10 years post-diagnosis, were used. Dietary intake was measured by 7-d dietary records. Validated questionnaires were used to measure health-related quality of life (HRQoL), fatigue and neuropathy. Confounder-adjusted linear regression models were used to analyse associations of each WCRF/AICR dietary recommendation with patient-reported outcomes. Higher vegetable intake (per 50 g) was associated with better global QoL ( β 2·6; 95 % CI 0·6, 4·7), better physical functioning (3·3; 1·2, 5·5) and lower levels of fatigue (−4·5; −7·6, −1·4). Higher fruit and vegetables intake (per 100 g) was associated with better physical functioning (3·2; 0·8, 5·5) and higher intake of energy-dense food (per 100 kJ/100 g) with worse physical functioning (−4·2; −7·1, −1·2). No associations of dietary recommendations with neuropathy were found. These findings suggest that adhering to specific dietary WCRF/AICR recommendations is associated with better HRQoL and less fatigue in CRC survivors. Although the recommendations regarding healthy dietary habits may be beneficial for the well-being of CRC survivors, longitudinal research is warranted to gain insight into the direction of associations.